2007
DOI: 10.1271/bbb.60328
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of the Mycorrhizal Basidiomycetes,Suillus grevilleiandS. bovinus, by Particle Bombardment

Abstract: Mycorrhizal basidiomycetes, Suillus grevillei and S. bovinus, were transformed by particle bombardment. We isolated eight and four transformants from S. grevillei and S. bovinus respectively under three conditions differing in terms of target distance and helium pressure. The transformation frequencies were 1.2 and 0.6 transformants/g DNA. Plasmid DNAs were integrated into the genomic DNA of the transformants and stably maintained. This is the first description of the transformation of S. grevillei and S. bovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The transformation efficiency for the generation of geneticin-resistant colonies did not differ significantly from that of the hygromicin-resistant colonies, and we confirmed that the setting combination of 1100 psi of helium pressure and a 6 cm target distance was more effective than other settings (data not shown). The settings established in this study were similar to those found for the biolistic transformation of mycelia of the mycorrhizal basidiomycetes Suillus grevillei and Suillus bovinus (Sunagawa et al 2007). …”
Section: Biolistic Variablessupporting
confidence: 73%
See 1 more Smart Citation
“…The transformation efficiency for the generation of geneticin-resistant colonies did not differ significantly from that of the hygromicin-resistant colonies, and we confirmed that the setting combination of 1100 psi of helium pressure and a 6 cm target distance was more effective than other settings (data not shown). The settings established in this study were similar to those found for the biolistic transformation of mycelia of the mycorrhizal basidiomycetes Suillus grevillei and Suillus bovinus (Sunagawa et al 2007). …”
Section: Biolistic Variablessupporting
confidence: 73%
“…(Sunagawa et al 2007), and Uromyces fabae (Djulic et al 2011). Because this method can deliver DNA directly into mycelia, protoplasts are not required.…”
Section: Introductionmentioning
confidence: 99%